EKSENTRISITAS DIGRAF PADA GRAF GIR MENGGUNAKAN ALGORITMA BREADTH FIRST SEARCH - Romario Marselino Barahama; Chriestie E.J.C. Montolalu; Rinancy Tumilaar (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2021)
Let  be a graph with the set of points  and the set of sides . The distance from point u to v in  is the length of shortest path from point  to , denoted by . The eccentricity of point  in graph  is the furthest distance from point to each in  denoted by . The point  is the eccentic point of  if . The purpose of this research is determine the eccentricity of the digraph on the gear graph  and determine the eccentricity of the digraph  gear graph using the breadth first search algorithm. The method used is to collect library sources in the form of books other refrences ehich are then used as the basis for conducting this research. Based on the discussion it can be concluded that the sahpe of eccentricity of the digraph on graph  is complete symetry with Graph Theory is the one of the math theory with mathematic knowledge using with ,  and , while for the eccentricity the digraph on the digraph gear  uses  breadth first search algorithm is ,  and .